COMPARATIVE STUDY ON UTILIZATION HELIUM AND CARBON DIOXIDE GAS AS A COOLANT AT HIGH TEMPERATURE ENGINEERING TEST REACTOR [HTTR] WITH MOX AND MINOR ACTINIDES AS A FUEL - FANISA FAUZIA, ARDITA
HTTR is one of reactor types which was developed by Japanese Government. The HTTR is a graphite moderator and helium gas-cooled reactor with 30 MW in thermal output and outlet coolant temperature of 950oC for high temperature test operation. In this study, we have utilized the different gas of coolant which is carbon dioxide and compared the results with helium. In addition to using the different type of gas for coolant, plutonium and minor actinides are also used as a fuel. Utilization of plutonium and minor actinide is one of the support system to non-proliferation issue in the nuclear development. The enrichment for uranium oxide were set 6-20% with plutonium and minor actinides concentration of 10%. First simulation is using helium as a coolant with plutonium and minor actinides as a fuel. The result for multiplication factor is higher than 1.0 at 17% enrichment of U-235, which means this reactor can achieved its critically condition. Whereas for carbon dioxide as a coolant with the same fuel, the result for multiplication factor is higher than 1.0 at 13% enrichment of U-235, which means that by using carbon dioxide as a coolant the reactor can achieve critically condition faster and higher than helium. In this study, burn up period is 1100 days. The reactor cell calculation was performed by using SRAC 2002 program, with nuclear data library was derived from JENDL3.2. Reactor core calculation was done by using CITATION module in 0-R–Z geometry.